Development of soil quality assessment framework: A comprehensive review of indicators, functions, and approaches - Ya’nan Fan; Chao Zhang; Wenyou Hu; Khalid Saifullah Khan; Yongcun Zhao; Biao Huang (Ecological Indicators)
Soil quality assessment research has progressively developed over four decades through sustained methodological advancements. However, the multifaceted nature of soil functions and complexity of assessment objectives and scales continue to pose significant challenges. In this study, bibliometric analysis was applied to systematically present the development of soil quality assessment research, elucidating the complex interrelationships among soil functions, assessment indicators, and approaches. The results indicated that while the volume of publications on soil quality assessment has steadily increased, with a notable surge between 2018 and 2022, the primary research topics remain focused on soil fertility and productivity, soil environment and safety, soil health and conservation, as well as soil assessment and management. The evolution of assessment objectives demonstrated a transition from singular functional focuses (fertility, environment, health) towards integrated multi-functional assessment approaches. Soil organic matter/ soil organic carbon (SOM/SOC) has been the most popular indicator for the assessment of soil quality due to its significant impact on various soil functions. However, the application of biological indicators in soil quality assessment remained limited, highlighting a gap between understanding and practice in soil quality research. Methodologically, assessment approaches exhibited progression from qualitative to quantitative paradigms. The rapid development of digital technologies presents both challenges and opportunities. Integrating artificial intelligence with multi-source data offers potential for rapid, real-time, large-scale monitoring and assessment of soil quality. This review retrospect the development trends and hotspots, more importantly, forecast the future work directions of soil quality assessment research.